(untitled) (The Research of Medical Science Review, 2025)
Background: Maintenance of adequate pupil size during phacoemulsification surgery is crucial for optimal surgical outcomes. Pharmacologic agents like nepafenac are commonly used to minimize pupil constriction during surgery. Objective: To compare the efficacy of 0.1% nepafenac eye drops with placebo (natural tears) in maintaining intraoperative pupil size during phacoemulsification surgery. Material and methods: This randomized controlled trial was carried out at Department of Ophthalmology, Hayatabad Medical Complex, from June 2022 to June 2023. In total,60 patients who were planned to undergo phacoemulsification surgery were selected and included into the study. Patients were then randomly divided into two groups; each group having a subject population of 30 patients. Group A was given 0.1% nepafenac eye drops while the control group, Group B, was given placebo which is the natural tears. Recruitment was done through a nonprobability consecutive sampling technique. Results: Mean diameter at the end of emulsification in group A was noted as 8.21±0.525mm compare to group B 8.06±0.718mm. Mean diameter at the end of surgery in nepafenac group versus placebo group was 7.89±0.350 vs 7.05±0.621mm respectively. The right eye was involved in 50% of cases in group A and 60% in group B, while the left eye was involved in 50% cases in group A and 40% cases of group B. Regarding the diameter difference, 83.3% of patients in group A experienced a pupil size reduction of ≤0.7mm compared to 23.3% in group B. Conversely, only 16.7% of cases in group A had a reduction >0.7mm, in contrast to 76.7% patients in group B. Conclusion: Nepafenac 0.1% significantly reduced pupil size constriction during phacoemulsification surgery compared to placebo, demonstrating its effectiveness in maintaining adequate pupil size and improving surgical outcomes. These findings highlight the utility of nepafenac in enhancing the efficiency and safety of cataract surgeries.